Electrochemical-Thermal Modeling to Evaluate Battery Thermal Management Strategies: II. Edge and Internal Cooling. Issue 1 (1st January 2015) - Bandhauer, Todd; Garimella, Srinivas; Fuller, Thomas F.
Abstract : A parameterized electrochemical model that predicts local reaction rate as a function of temperature, depth of discharge, and overpotential was developed in Part 1 of this study using temperature-dependent performance data. In Part 2, this model was extended to incorporate non-ideal current collection, which induces localized heating near the tabs, using a quasi-three-dimensional domain. This model was used to study the effect of edge cooling the cell, which was shown to impose substantial thermal gradients and temperature increases. The large temperature difference observed for this cooling method leads to significant non-uniform cycling, which can lead to premature aging. In addition, the performance of a cell with an innovative internal cooling system that utilized passive microchannel liquid-vapor phase change was also investigated. Because of the substantially reduced thermal resistance from the heat source to the cooling fluid, the charge and discharge energy extraction density was highest for the internal cooling system in spite of the cell-level volume increase. Furthermore, the saturation temperature of the phase change fluid can be optimized to balance capacity fade and energy extraction at elevated temperatures, yielding systems much smaller than the most compact conventional external cooling system.